Estrutura de uma taxocenose de anfíbios anuros em fragmento urbano de floresta atlântica no extremo leste da região neotropical - Leite Filho, Edinaldo (2013)
Based on diet, microhabitat use and morphometry data, we investigated the importance of ecological and historical (phylogenetic) factors an anuran assemblage (16 species) in a urban fragment of Atlantic Rainforest in northeast Brazil. The niche breadth for microhabitat use was low for all species, while diet niche breadth was high for the majority. The main food categories were Coleoptera and Orthoptera, and the close related species showed distinct diet. The pseudo-community analysis indicated the presence of structure for diet and microhabitat use. The canonical phylogenetic ordination detected historical effects in microhabitat use and morphology for Hylidae and Leptodactylidae. However, none historical effect was found for diet. Then, we conclude that the structure found in null models is phylogenetic for microhabitat and ecological for diet. Nevertheless, it can be stated that recent perturbations could be more important in structure assemblage, due to low diversity and great diet plasticity of species, indicating possible ecological release.